2015
DOI: 10.1002/gcc.22241
|View full text |Cite
|
Sign up to set email alerts
|

Microarray analysis of differentially expressed genes in ovarian and fallopian tube epithelium from risk‐reducing salpingo‐oophorectomies

Abstract: Mutations in the BRCA1 and BRCA2 genes confer an increased lifetime risk for breast and ovarian cancer. Ovarian cancer risk can be decreased by risk-reducing salpingo-oophorectomy (RRSO). Studies on RRSO material have altered the paradigm of serous ovarian cancer pathogenesis. The purpose of this study was to identify candidate genes possibly involved in the pathogenesis of serous ovarian cancer by carrying out a microarray analysis of differentially expressed genes in BRCA1/2- mutation positive ovarian and fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 62 publications
1
4
0
Order By: Relevance
“…This is consistent with the surgicopathologic study of gynecologic cancers identified in >1,000 women who underwent risk reducing salpingooophorectomy, in which approximately equal proportions of ovarian and fallopian tube cancers were identified (44). It is further supported by the finding in genome-wide expression studies of numerous differentially expressed genes in both ovaries and fallopian tubes in women at high ovarian cancer risk (45). In addition, a recent series using detailed genomic analysis of serous tubal intraepithelial carcinomas (STICs), invasive fallopian tube lesions, invasive ovarian lesions, and omental metastases, demonstrated that although at least half of cases had a STIC as a precursor lesion, some STICs represented intraepithelial metastases to the fallopian tube (46).…”
Section: Discussionsupporting
confidence: 87%
“…This is consistent with the surgicopathologic study of gynecologic cancers identified in >1,000 women who underwent risk reducing salpingooophorectomy, in which approximately equal proportions of ovarian and fallopian tube cancers were identified (44). It is further supported by the finding in genome-wide expression studies of numerous differentially expressed genes in both ovaries and fallopian tubes in women at high ovarian cancer risk (45). In addition, a recent series using detailed genomic analysis of serous tubal intraepithelial carcinomas (STICs), invasive fallopian tube lesions, invasive ovarian lesions, and omental metastases, demonstrated that although at least half of cases had a STIC as a precursor lesion, some STICs represented intraepithelial metastases to the fallopian tube (46).…”
Section: Discussionsupporting
confidence: 87%
“…Loss of ZFP36 expression has been associated with metastasis (20). A study by Veskimäe et al (38) identified ZFP36 as one of the most downregulated genes when the authors compared the gene expression in BRCA1 / 2 germline mutated tubal and ovarian tissues (removed by risk-reducing salpingo-oophorectomy) with that in healthy control tissues, thus supporting a role for ZFP36 in ovarian carcinogenesis.…”
Section: Discussionmentioning
confidence: 97%
“…Specifically, HRD exhibits a distinct core GEP [ 88 ]. Notably, in the context of gBRCA1* , even healthy fallopian tissue exhibits a specific GEP, suggesting an epigenome-modifying influence [ 89 , 90 ]. The partial divergence observed between BRCA1* and BRCA2* tumors probably relies on the pleiotropic function of BRCA1, which is not restricted to DSB management [ 91 , 92 ].…”
Section: From Ovarian Cancer Genetics To Homologous Recombination Def...mentioning
confidence: 99%